Tidal regime along Vietnam coast under impacts of sea level rise - Thuc, Tran; Son, Duong Hong (VNU Journal of Science: Earth and Environmental Sciences; Vol 28 No 2, 2012)
Abstract . The characteristics of the tides in coastal areas are formed by the resonance between the astronomical waves transmitted from the ocean into shallow water and topography in both horizontal (scale of water bodies) and vertical (depth) directions. Thus, sea level rise due to climate change that would alter the depth and scale of the ocean will lead to changes in tidal characteristics. The ROMS model (Regional Oceanography Modeling System) was used to study the impact of sea level rise on tidal regime along the coast ofVietnam. The model was validated by using tidal current regime, and, consequently, used to simulate for the cases of global sea level rise scenarios of 0.5m, 0.75m and 1.0 m. Keywords: Tidal regime, mean sea level, coast ofVietnam.